MANAJEMEN PENDIDIKAN KARAKTER RELIGIUS DI ERA PANDEMI COVID-19 DI SDMT PONOROGO - Abidin, Jainal; Syarifan Nurjan; Anip Dwi Saputro (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2023)
This study describes the management of religious character education in the Covid-19 pandemic era at SDMT Ponorogo. The objectives to be achieved are: (1) to determine the management of religious character education in the Covid-19 pandemic era at SDMT Ponorogo, and (2) to determine the supporting and inhibiting factors in its implementation. Data collection was carried out using observation, interview, and documentation methods. The collected data were analyzed using data reduction, data presentation, and data conclusion methods. The results of this study are as follows: (1) planning for religious character education in the Covid-19 pandemic era at SDMT Ponorogo was carried out by determining the goals and targets of religious character education, compiling the types of content, programs, activities and policies, then by creating activity programs, and by preparing tools for implementing activities. (2) Organizing religious character education in the Covid-19 pandemic era at SDMT Ponorogo was carried out by dividing tasks and responsibilities, preparing activity schedules, and fostering the relevant units. (3) The implementation of religious character education in the Covid-19 era at SDMT Ponorogo is carried out by strengthening religious character through online, offline, limited face-to-face, and normal face-to-face learning. (4) Supervision of religious character education in the Covid-19 era at SDMT Ponorogo includes: preliminary or feed-forward supervision, ongoing supervision, and feedback supervision.